2013
DOI: 10.1186/1748-717x-8-41
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of ischemic stroke in cervical cancer patients: a nationwide population-based study

Abstract: BackgroundIncreased risk of ischemic stroke has been validated for several cancers, but limited study evaluated this risk in cervical cancer patients. Our study aimed to evaluate the risk of ischemic stroke in cervical cancer patients.MethodsThe study analyzed data from the 2003 to 2008 National Health Insurance Research Database (NHIRD) provided by the National Health Research Institutes in Taiwan. Totally, 893 cervical cancer patients after radiotherapy and 1786 appendectomy patients were eligible. The Kapla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 22 publications
3
24
0
Order By: Relevance
“…1,2,[15][16][17][18][19] In a recent study of patients with breast, colorectal, lung, or prostate cancer in the United States, the 1-year cumulative incidence of ischemic/hemorrhagic stroke was increased by 1.3/1.6 in those with colorectal cancer and 1.8/3.4 in those with lung cancer but not in those with breast or prostate cancer, 2 as in our study. In a study of patients with cancers at 34 sites in the Swedish Registry of Cancers, the risks for ischemic/hemorrhagic stroke within 6 months of cancer diagnosis were increased by 1.6/2.2 for 18/20 cancer sites.…”
Section: July 2018supporting
confidence: 66%
See 1 more Smart Citation
“…1,2,[15][16][17][18][19] In a recent study of patients with breast, colorectal, lung, or prostate cancer in the United States, the 1-year cumulative incidence of ischemic/hemorrhagic stroke was increased by 1.3/1.6 in those with colorectal cancer and 1.8/3.4 in those with lung cancer but not in those with breast or prostate cancer, 2 as in our study. In a study of patients with cancers at 34 sites in the Swedish Registry of Cancers, the risks for ischemic/hemorrhagic stroke within 6 months of cancer diagnosis were increased by 1.6/2.2 for 18/20 cancer sites.…”
Section: July 2018supporting
confidence: 66%
“…Another Swedish study on manifest breast cancer, with 5.7 years of follow-up, found a slightly increased risk of ischemic stroke (RR, 1.12) but not for hemorrhagic stroke. 17 Focus has been on the interaction between cancer and the clotting cascade in the search for an explanation for cancer patient's increased risk of stroke; the literature contains ample evidence of this interaction. 20,21 Our study was not designed to investigate causes of stroke in cancer, but our findings nevertheless point in the direction of possible causal relationships.…”
Section: July 2018mentioning
confidence: 99%
“…Data from the National Health Insurance Research Database of Taiwan showed a >50% increase in the risk of ischemic stroke for women treated with RT involving the neck for cervical cancer 24. In that study, the investigators postulated that the elevated stroke risk was primarily related to systemic injury caused by RT.…”
Section: Discussionmentioning
confidence: 99%
“…23 Although there are no available prior studies investigating the relationship between HPV status and CVEs in RT-treated HNCA patients, multiple investigators have reported parallel findings in other populations that are supportive of the current results. 12,24,25 Data from the National Health Insurance Research Database of Taiwan showed a >50% increase in the risk of ischemic stroke for women treated with RT involving the neck for cervical cancer. 24 In that study, the investigators postulated that the elevated stroke risk was primarily related to systemic injury caused by RT.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Although cervical cancer of females has declined in Taiwan since beginning in 1995 because National Health Insurance (NHI) has provided free mass screening of cervical neoplasia since 1995. The national Pap smear screening program significantly reduced cervical cancer risk explaining the dramatic decline in invasive cancer incidence after 1996.…”
Section: Introductionmentioning
confidence: 99%